Skilled labour and international specialisation in the Caribbean region - Iyare, Sunday Osaretin (Caribbean Centre for Monetary Studies [St. Augustine]TT, 2003)
Argues that the development of human capital and skilled labour would become increasingly important determinants of industrial localization in the new Caribbean Single Market Economy.